ANALISIS MANAJEMEN RISIKO PEMBIAYAAN: FAKTOR PENYEBAB DAN STRATEGI PENANGANAN NASABAH BERMASALAH PADA BANK SYARIAH INDONESIA KCP SURABAYA PELINDO PLACE - Salsabillah, Alda; Shafira, Adinda; Amelia, Nadya (Jurnal Syariah dan Ekonomi Islam, 2026)
This study aims to analyze in depth the implementation of risk management in handling problematic customers at Bank Syariah Indonesia (BSI) KCP Surabaya Pelindo Place. This research uses a qualitative descriptive approach with data collection techniques including interviews, observations, and documentation. The results show that risk management has been implemented through systematic stages: risk identification, measurement, monitoring, and control. Problematic financing is addressed through restructuring strategies such as rescheduling, reconditioning, and restructuring. However, the effectiveness is influenced by internal factors such as customer behavior and external factors such as economic conditions. Strengthening risk mitigation and customer literacy is necessary to improve financing quality.